The reasons for skepticism determining public attitudes toward social responsibility - Telyčėnaitė, Austė (Information & Media, 2017)
Although the idea of social responsibility is mainly targeted at the well-being of the society, due to certain dishonesties of businesses, unethical communication or the skeptical nature of the population, the outlook of the general population is skeptical toward social responsibility activities. The article aims to present the public attitudes toward different social responsibility activities carried out by organizations, as well as the causes and consequences these attitudes are determined by. The article deals with social responsibility and the problems caused by the different approaches regarding it. An analysis of foreign literature revealed that there is a predominant skeptical approach to social responsibility. The article presents a qualitative study, which reveals the public attitudes toward the social responsibility of organizations and their communication. The results of the research revealed that skepticism with regard to social responsibility is most often determined by the personal experiences of individuals rather than social responsibility-related events. It was also revealed that skepticism, with regard to social responsibility, hinders the development of social responsibility initiatives and demotivates organizations to become socially responsible. Although research of foreign authors reveals that skepticism negatively impacts consumer intentions to purchase various goods, the study showed that in a local context, skepticism is irrelevant.